2017
DOI: 10.1002/adsc.201701107
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of 3,3’‐Bisindolines by Organocatalytic Michael Additions of Fluorooxindole Enolates to Isatylidene Malononitriles in Aqueous Solution

Abstract: A highly diastereoselective organocatalytic reaction for the synthesis of fluorinated 3,3′-bisindolines exhibiting adjacent tetrasubstituted carbon stereocenters is described. A broad variety of heterochiral bisindolines was prepared in 91-99% yield using 3-fluorooxindoles and isatylidene malononitriles in the presence of catalytic amounts of triethylamine in water or aqueous solution. The reaction can be upscaled without compromising yield and diastereoselectivity and the general usefulness of this method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Having established a profound interest in organofluorine chemistry, 32 33 34 35 36 37 38 39 40 including C–F bond activation methodology and synthetic or chiroptical sensing applications thereof, 19,21 , 41–43 we decided to investigate the possibility of practical alkyl fluoride to iodide conversion, which would also enable subsequent nucleophilic displacements or other reactions. Hilmersson and co-workers showed that this is possible with YbI 3 (THF) 3 , which has to be prepared from expensive ytterbium(II) iodide (Scheme 1 ).…”
Section: Table 1 Optimization Of the Csp ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Having established a profound interest in organofluorine chemistry, 32 33 34 35 36 37 38 39 40 including C–F bond activation methodology and synthetic or chiroptical sensing applications thereof, 19,21 , 41–43 we decided to investigate the possibility of practical alkyl fluoride to iodide conversion, which would also enable subsequent nucleophilic displacements or other reactions. Hilmersson and co-workers showed that this is possible with YbI 3 (THF) 3 , which has to be prepared from expensive ytterbium(II) iodide (Scheme 1 ).…”
Section: Table 1 Optimization Of the Csp ...mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] In addition, several laboratories, including ours, have been able to demonstrate carbon-fluoride bond functionalization with unactivated aliphatic substrates although the need for harsh conditions, together with low functional group tolerance and competing side reactions continue to limit the general scope in some cases. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Scheme 1 C-F Bond functionalization with metal iodides 49 Having established a profound interest in organofluorine chemistry, [32][33][34][35][36][37][38][39][40] including C-F bond activation methodology and synthetic or chiroptical sensing applications thereof, 19,21,[41][42][43] we decided to investigate the possibility of practical alkyl fluoride to iodide conversion, which would also enable subsequent nucleophilic displacements or other reactions. Hilmersson and co-workers showed that this is possible with YbI 3 (THF) …”
mentioning
confidence: 99%
“…Based on our longstanding interest in fluorinated compounds, 7,9–20 we decided to screen a variety of chiral stationary phases (CSPs) to separate the enantiomers of the 2‐aryl‐2‐fluoroacetonitriles 1 – 10 by liquid chromatography, Figure 1. It was expected that the development of high performance liquid chromatography (HPLC) conditions that allow baseline separation of 1 – 10 would not be a simple task and most likely be achieved with some of the most frequently used CSPs originally introduced by Pirkle and Okamoto who without a doubt have been the most influential inventors of broadly useful chiral HPLC columns 21–27 .…”
Section: Introductionmentioning
confidence: 99%
“…10 In this context, the construction of chiral 3-substituted 3-fluoroindolinones containing a -amine fragment has aroused great interest among researchers. 7,8,11,12 In recent years, some progress has been made. In 2017, Song 13 and co-workers reported the asymmetric Mannich reaction of 3-fluorooxindoles with -amidosulfones via cooperative cation-binding catalysis, and -fluoro--amino-oxindoles were obtained in excellent enantioselectivities and moderate to excellent diastereoselectivities (Scheme 1).…”
mentioning
confidence: 99%